Serum Detection of Anti-thyroid Peroxidase and Anti-thyroglobulin Antibodies in Chinese Patients With Pemphigus Vulgaris and Pemphigus Foliaceus and Literature Review - Wang, He-Xiao; Yang, Yang; Hu, Jing-Yuan; Zhang, Li-Ming; Cai, Yun-Fei; Guo, Hao; Xiao, Ting; Chen, Hong-Duo; Gao, Xing-Hua; Qiao, Shuai (Frontiers in Immunology, 2021)
Background: Pemphigus is a rare but life-threatening autoimmune skin disease characterized by blistering on skin and/or mucous membranes. The physiological process of blister formation involves IgG antibodies against the desmogleins (Dsgs) and desmocollins (Dscs). Additional autoAbs have also been suggested to mediate the disease heterogeneity, such as anti-thyroid peroxidase (anti-TPO) and antithyroglobulin (anti-Tg) antibodies, the essential culprits of the immune system in autoimmune thyroid diseases. Purpose: To investigate the levels and antibody positivity of anti-TPO and anti-Tg antibodies in pemphigus patients. Methods: Antibody positivity and levels of anti-TPO and anti-Tg antibodies in pemphigus patients as compared to healthy controls were examined. A meta-analysis was conducted by reviewing six similar studies. Results: 98 Chinese pemphigus patients and 65 healthy controls were enrolled in the study. Our meta-analysis revealed a significant correlation between increased presence of positive anti-TPO and anti-Tg antibodies and pemphigus, particularly for pemphigus vulgaris (PV). Such correlation was also observed in our own hospitalized PV patients, but not in pemphigus foliaceus (PF) patients. In addition, the status of anti-TPO and anti-Tg antibodies were also compared between females and males within PV patients, PF patients or controls, as well as compared for females or males between pemphigus patients and controls. In the analysis of T cell counts, we found abnormal low CD3 + T cell counts (< 690 n/µl) were only detected in patients whose thyroid antibody levels were less than 20 IU/ml. Conclusion: Pemphigus patients showed higher levels and antibody positivity of anti-TPO and anti-Tg antibodies than healthy controls. Further investigations are needed to identify the pathogenic functions of these antibodies in pemphigus, as well as to identify the potential shared susceptibility genes.